The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1161/circgenetics.113.000412
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies Variants in Casein Kinase II ( CSNK2A2 ) to be Associated With Leukocyte Telomere Length in a Punjabi Sikh Diabetic Cohort

Abstract: Background Telomere length is a heritable trait and short telomere length has been associated with multiple chronic diseases. We investigated the relationship of relative leukocyte telomere length (RTL) with cardiometabolic risk and performed the first GWAS and meta-analysis to identify variants influencing RTL in a population of Sikhs from South Asia. Methods and Results Our results revealed a significant independent association of shorter RTL with type 2 diabetes (T2D) and heart disease. Our discovery GWAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 53 publications
0
48
0
Order By: Relevance
“…We carried out a two stage GWAS of 25(OH)D levels in a total of 3538 subjects comprised of 1387 individuals in a ‘discovery sample set’ and 2151 individuals in an independent ‘replication sample set’ from the AIDHS/SDS, described earlier [11,12]. All individuals in this study were recruited from the single geographical location of the state of Punjab, India.…”
Section: Methodsmentioning
confidence: 99%
“…We carried out a two stage GWAS of 25(OH)D levels in a total of 3538 subjects comprised of 1387 individuals in a ‘discovery sample set’ and 2151 individuals in an independent ‘replication sample set’ from the AIDHS/SDS, described earlier [11,12]. All individuals in this study were recruited from the single geographical location of the state of Punjab, India.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 However, other genome-wide association studies have identified single-nucleotide polymorphisms associated with TL, which do not contain candidate genes of telomere biology, but rather genes related to several cancers and other diseases. 19,20 Recently, Saxena et al 21 showed that variants in casein kinase II (CSNK2A2) are associated with leukocyte TL in a Punjabi Sikh Diabetic Cohort.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%
“…23 rs1046623910:43849827 FXYD4 , RASGEF1A T0.074.51 d 7.00E-60.11−0.02980.452rs345963856:141926004 AK097143 T0.05−4.53 d 6.00E-60.01−0.08910.513rs117873418:19102564 LOC100128993 A0.064.91 d 9.00E-70.070.03200.520rs1090488710:17188641 TRDMT1 T0.474.61 d 4.00E-60.81−0.01300.697rs168591403:111792594 TMPRSS7 C0.284.58 d 5.00E-60.11−0.01510.697rs7339483822:30225973 ASCC2 G0.064.44 d 9.00E-60.270.005410.839rs490210014:62549819 SYT16 G0.284.64 d 4.00E-60.23−0.00110.968rs76804684:108304199 DKK2 , PAPSS1 T0.03−5.47 d 5.00E-80.02−0.00250.978Saxena et al . 24 rs20987135:37144574 C5orf42 T0.47−0.253.00E-60.76−0.05430.058rs7401982816:58209274 CSNK2A2 A0.16−0.385.00E-80.05−0.00740.899Gu et al . 25 rs602846620:38129002 DHX35 ANR e 0.1923.00E-70.25−0.04730.103rs6541286:117086378 KPNA5 TNR e 0.1223.00E-60.09−0.05880.151rs6215591:43645411 WDR65 ANR e 0.16…”
Section: Resultsmentioning
confidence: 99%